The Use of Simulation in Physician Assistant Programs: A National Survey. Issue 4 (December 2017) - Coerver, Donald; Multak, Nina; Marquardt, Ashley; Larson, Eric H.
Abstract : Purpose: The purpose of this study was to develop a national-level description of the current use of simulation activities in physician assistant (PA) education and to assess the degree to which the use of simulation varies by PA program size and institutional type. Methods: An electronic survey on medical simulation was sent to 177 PA program directors or to a designated simulation activities coordinator, using the directory on the Physician Assistant Education Association website. The survey addressed program characteristics, types of simulation modalities in use, and frequency of use of those modalities in PA training. The specific content areas addressed were error disclosure, medical knowledge, patient care, and psychomotor skills. Results: The survey was emailed 3 times from early April to mid-May 2014, with a follow-up call to nonrespondents in August 2014. Of the 177 PA programs contacted, 63 completed the survey, for a response rate of 35.6%. Results indicate widespread use of simulation by survey respondents, especially in teaching, assessment of medical knowledge, and clinical skills, with somewhat lower levels of use in content areas such as error disclosure, delivery of bad news, and team training. Conclusions: Although barriers exist to its use in training health care professionals, simulation has become an important tool for training PAs in a variety of medical and interpersonal skills. It is also clear that simulation is an important tool for conducting interprofessional training. More research is needed to identify optimal approaches to the use of simulation in health care professions training.